Further evidence of third party unresponsiveness in immunologically tolerant animals - Zeiss, Irmgard M. (1969)
Three instances of third party unresponsiveness in immunologically tolerant mice are reported. Tolerance was induced across the H-2 barrier. Runt disease was prevented by the use of (host × donor)F(1) hybrid cells for tolerance induction. The rejection of third party grafts by F(1) hybrids from crosses between the host strain and the tolerance inducing donor strain excluded antigenic overlap as a possible explanation for the phenomenon. Third party unresponsiveness was restricted to weak histocompatibility antigens. Skin grafts presenting the tolerant hosts with third party H-2 antigens were rejected with normal promptitude. CBA mice tolerant of A, and A mice tolerant of CBA retained C3H grafts significantly longer than (A × CBA)F(1) hosts. It is suggested that this instance of third party unresponsiveness in reciprocally tolerant animals favours the interpretation that the phenomenon is due to incomplete specificity of induced immunological tolerance, rather than to an innate inability of the tolerant hosts to react against the relevant third party histocompatibility antigens.